2017
DOI: 10.7150/jca.20835
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Alone or Concurrent Chemoradiation for Esophageal Squamous Cell Carcinoma in Elderly Patients

Abstract: Purpose: The reported data of elderly ESCC are rather limited and there is a lack of information to guide treatment decisions for elderly patients with esophageal cancer. This study aims to identify the efficacy and factors for optimal treatment approaches for elderly esophageal squamous cell carcinoma (ESCC) treated with radiotherapy (RT) alone or concurrent chemoradiation (CCRT).Methods: This study included 184 I-III elderly ESCC patients aged ≥70 years treated by oral single agent CCRT (sCCRT) or double age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
3
17
2
Order By: Relevance
“…One reason for these may be that our study included a relatively large number of patients with early-stage cancers. Age is an independent prognostic factor of OS in our study, which is different from the results of other studies (14,18,23). Huang et al suggested EC patients aged ≥80 benefit from RT only if the cancer is in localized/regional stage (24).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…One reason for these may be that our study included a relatively large number of patients with early-stage cancers. Age is an independent prognostic factor of OS in our study, which is different from the results of other studies (14,18,23). Huang et al suggested EC patients aged ≥80 benefit from RT only if the cancer is in localized/regional stage (24).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that RT in older patients resulted in good OS, with 2-year estimated OS, DFS, and LRC of 53%, 42%, and 51%, respectively, and a median OS time of 30 months ( Figure 1). Interestingly, our results were comparable to or slightly better than those of previous studies on patients younger than those in our study (14,18,(21)(22)(23) (Table V). In addition, only 10% of patients failed at distant sites, which is relatively low compared to the literature in which about 13-37% is expected (7,8,14,18,23).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Several studies had proven that dual-agent therapy achieved superior survival than single-agent CRT for elderly patients with ESCC [20,21]. Zhao et al demonstrated that CRT with a single agent in elderly patients had a similar survival benefit compared to CRT with a dual agent, accompanied by less toxicity [22]. Similar to Zhao et al, in the current study, the survival of patients treated with CRT with various CC regimens or CC cycles did not alter significantly.…”
Section: Discussionsupporting
confidence: 78%